1996
DOI: 10.1084/jem.184.4.1365
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of Cas-L, a 105-kD Crk-associated substrate-related protein that is involved in beta 1 integrin-mediated signaling in lymphocytes.

Abstract: SummaryI.ntegrin/hgand binding evokes tyrosine phosphorylation of various proteins. We reported previously that a 105 kD protein (ppl05) was tyrosine phosphorylated by the engagement of [31 integrins in T lymphocytes. We show here that ppl05 is a novel p130Cas (Crk-associated substrate)-related protein. Deduced amino acid sequence revealed that ppl05 contains conserved motifs with p130Cas, and both ppl05 and p130Cas bind to focal adhesion kinase (pp125FAK) and Crk. However, ppl05 has a clearly distinct structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
139
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(144 citation statements)
references
References 39 publications
4
139
0
1
Order By: Relevance
“…29,30 CAS (for Crk-associated substrate) was cloned as a major 130 kDa tyrosine phosphorylated protein in response to v-crk transformation. 27 Currently, there are three CAS-related molecules (the 130 kDa protein CAS, the 110 kDa protein HEF1/CAS-L, 67,68 and the 95 kDa protein SIN/EFS 69,70 ). The structure for CAS-family members includes an amino-terminal SH3 domain, multiple YXXP motifs (substrate domain), and potential SRC-binding sites at the Cterminus.…”
Section: Cas Hef1mentioning
confidence: 99%
“…29,30 CAS (for Crk-associated substrate) was cloned as a major 130 kDa tyrosine phosphorylated protein in response to v-crk transformation. 27 Currently, there are three CAS-related molecules (the 130 kDa protein CAS, the 110 kDa protein HEF1/CAS-L, 67,68 and the 95 kDa protein SIN/EFS 69,70 ). The structure for CAS-family members includes an amino-terminal SH3 domain, multiple YXXP motifs (substrate domain), and potential SRC-binding sites at the Cterminus.…”
Section: Cas Hef1mentioning
confidence: 99%
“…Later on, its role in intracellular signalling and regulation of cytoskeleton has been further characterized. Several reports demonstrated that HEF1 is mainly expressed in lymphoid and epithelial cells [2,3]. It has been implicated in signalling pathways initiated by ligation of integrins or antigen on BCR or TCR [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HEF1 expression varies considerably between different cell types and tissues. 71,72,96,97 It is most abundant in vivo in tissues with polarized cell populations, including epithelial cells, neuronal and glial cells, and lymphoid cells, and its signaling action may be particularly important in these cell lineages. 97,98 p130Cas is abundant at all phases of cell cycle.…”
Section: Introduction To Hef1mentioning
confidence: 99%